Positive electrode active material precursor, its manufacturing method and positive electrode active material

The core-shell structured positive electrode active material precursor addresses capacity, life, and resistance issues in lithium batteries by optimizing particle orientation and composition, enhancing battery performance through controlled reaction processes.

JP7625329B2Active Publication Date: 2025-02-03LG CHEM LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023530055
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-12-01
Filing Date
2021-12-01
Publication Date
2025-02-03
Estimated Expiration
2041-12-01

AI Technical Summary

Technical Problem

Lithium composite metal oxides used in positive electrodes of secondary batteries face issues with capacity, life, and resistance characteristics due to side reactions during doping or surface coating, leading to deformation and performance degradation.

Method used

A positive electrode active material precursor is formed with a spherical structure composed of randomly oriented primary particles, featuring a core-shell configuration with specific compositions and orientations, including a first core portion, a first shell portion, and a second shell portion, which are formed through controlled reaction processes using transition metal solutions and ammonium cation complexes.

Benefits of technology

The precursor and resulting active material enhance capacity, life, and resistance characteristics by minimizing side reactions and improving doping efficiency, resulting in improved battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007625329000002
    Figure 0007625329000002
  • Figure 0007625329000003
    Figure 0007625329000003
  • Figure 0007625329000004
    Figure 0007625329000004
Patent Text Reader

Abstract

The present invention relates to a cathode active material precursor, which includes a first core portion, which is a spherical secondary particle formed by aggregation of primary particles and is made of randomly oriented primary particles; a first shell portion, which is formed on the first core portion and is made of primary particles whose (001) plane is oriented in a direction from the center toward the surface of the secondary particle; and a second shell portion, which is formed on the first shell portion and is made of randomly oriented primary particles; a method for producing the same; and a cathode active material produced thereby.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2020-0165675, filed December 1, 2020, the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to a positive electrode active material precursor capable of realizing a secondary battery excellent in capacity characteristics, life characteristics and resistance characteristics, a method for producing the same, and a positive electrode active material. [Background technology]

[0003] Recently, with the technological development and increasing demand for mobile devices and electric vehicles, the demand for secondary batteries as energy sources is rapidly increasing. Among such secondary batteries, lithium secondary batteries, which have high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used.

[0004] Lithium transition metal oxides such as lithium cobalt oxides (LiCoO2), lithium nickel oxides (LiNiO2), lithium manganese oxides (LiMnO2 or LiMn2O4), and lithium iron phosphate (LiFePO4) have been developed as positive electrode active materials for lithium secondary batteries. a Co b Mn c ]O2, Li[Ni a Co b Al c ]O2, Li[Ni a Co b Mn c Al d Lithium composite transition metal oxides containing two or more transition metals, such as ]O2, have been developed and are widely used.

[0005] In the case of the lithium composite transition metal oxide containing two or more kinds of transition metals described above, a method of doping with a doping element or coating the surface is used to improve the battery performance and stability.

[0006] However, when doping or coating the surface with a doping element, undesirable substances may be generated on the surface of the positive electrode active material due to side reactions, or the shape or orientation of the primary particles contained in the positive electrode active material may be deformed, resulting in problems such as reduced capacity, lifespan, or resistance characteristics of the battery when applied to the battery.

[0007] Therefore, there is a need for a positive electrode active material that can improve the capacity, life and resistance characteristics of a battery. Summary of the Invention [Problem to be solved by the invention]

[0008] The present invention has been made to solve the above-mentioned problems, and has an object to provide a positive electrode active material precursor and a positive electrode active material that can realize a secondary battery excellent in capacity characteristics, life characteristics and resistance characteristics. [Means for solving the problem]

[0009] The present invention provides a positive electrode active material precursor, which comprises a first core portion that is a spherical secondary particle formed by aggregation of primary particles and is made of randomly oriented primary particles, a first shell portion that is formed on the first core portion and is made of primary particles whose (001) planes are oriented in a direction from the center to the surface of the secondary particle, and a second shell portion that is formed on the first shell portion and is made of randomly oriented primary particles.

[0010] The present invention also provides a method for producing a cathode active material precursor according to the present invention, comprising the steps of: (A) introducing a transition metal-containing solution containing nickel (Ni), cobalt (Co) and manganese (Mn) ions, an ammonium cation complexing agent, and a basic solution into a reactor and carrying out a coprecipitation reaction to form a first core portion; (B) introducing the transition metal-containing solution, the ammonium cation complexing agent, and a basic solution into a reactor containing the first core portion and carrying out a coprecipitation reaction to form a first shell portion on the first core portion; and (C) introducing the transition metal-containing solution, the ammonium cation complexing agent, a basic solution, and a third doping solution containing M3 (one or more elements selected from Nb, Ti, Al, Mo, W, Ta, V, and La) ions into a reactor containing the first shell portion formed on the first core portion and carrying out a coprecipitation reaction to form a second shell portion on the first shell portion, wherein the coprecipitation reaction in the step (B) is carried out at a lower pH than the coprecipitation reaction in the step (A).

[0011] The present invention also provides a positive electrode active material comprising a second core portion which is a spherical secondary particle formed by aggregation of primary particles and which is made of randomly oriented primary particles, a third shell portion which is formed on the second core portion and which is made of rod-shaped primary particles whose (003) planes are oriented in a direction from the center to the surface of the secondary particle, and a fourth shell portion which is formed on the third shell portion and which is made of randomly oriented primary particles. Effect of the Invention

[0012] The positive electrode active material precursor according to the present invention includes a first core portion made of randomly oriented primary particles, a first shell portion formed on the first core portion and made of primary particles whose (001) planes are oriented in a direction from the center to the surface of the secondary particles, and a second shell portion formed on the first shell portion and made of randomly oriented primary particles. The orientation of the positive electrode active material precursor remains in a positive electrode active material produced by calcining the positive electrode active material precursor, thereby enabling the capacity characteristics, life characteristics, and resistance characteristics to be improved. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 is a schematic diagram of a positive electrode active material precursor according to the present invention. [Diagram 2] FIG. 1 is a schematic diagram of a positive electrode active material according to the present invention. [Diagram 3] 1A is a SEM image of a cross section of the positive electrode active material precursor of Example 1, and FIG. 1B is a TEM image of a first shell portion of the positive electrode active material precursor of Example 1. [Figure 4] 1A is a SEM image of a cross section of the positive electrode active material of Example 1, and FIG. 1B is a TEM image of the third shell portion and the fourth shell portion of the positive electrode active material of Example 1. [Diagram 5] 1 shows SEM images of (A) a positive electrode active material precursor and (B) a positive electrode active material in Example 1. [Figure 6] 1 shows SEM images of (A) a positive electrode active material precursor and (B) a positive electrode active material in Example 2. [Figure 7] 1 shows SEM images of (A) a positive electrode active material precursor and (B) a positive electrode active material in Example 3. [Figure 8] 1A shows SEM images of a positive electrode active material precursor, (B) a cross section of the positive electrode active material precursor, (C) a positive electrode active material, and (D) a cross section of the positive electrode active material in Comparative Example 1. [Figure 9] 1A shows SEM images of a positive electrode active material precursor, (B) a cross section of the positive electrode active material precursor, (C) a positive electrode active material, and (D) a cross section of the positive electrode active material of Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of ​​the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.

[0015] In this specification, the terms "comprise", "comprise", "have" and the like are intended to specify the presence of embodied features, numbers, steps, components, or combinations thereof, but are not intended to preclude the presence or additional possibility of one or more different features, numbers, steps, components, or combinations thereof.

[0016] In this specification, D 50 and D can be defined as the particle size that corresponds to 50% of the cumulative volume in the particle size distribution curve (graph curve of particle size distribution degree). 50 can be measured by using, for example, a laser diffraction method. The laser diffraction method generally allows measurement of particle sizes from the submicron range to several mm, and can provide results with high reproducibility and high resolution.

[0017] As used herein, the term "on" is meant to include not only cases where one structure is formed immediately on top of another structure, but also cases where a third structure is interposed between the structures.

[0018] In this specification, the term "primary particle" refers to the smallest particle unit that can be distinguished as a single mass when a cross-section of a positive electrode active material is observed with a scanning electron microscope (SEM), and may consist of one crystal grain or multiple crystal grains.

[0019] In this specification, the term "secondary particle" refers to a secondary structure formed by the aggregation of a plurality of primary particles.

[0020] The present inventors have discovered that when a positive electrode active material is produced using a positive electrode active material precursor having a specific shape, the produced positive electrode active material also has a specific shape, and when the positive electrode active material is applied to a secondary battery, the capacity characteristics and life characteristics of the battery are improved, thereby completing the present invention.

[0021] Positive electrode active material precursor The positive electrode active material precursor according to the present invention is a spherical secondary particle formed by aggregation of primary particles, and includes a first core portion made of randomly oriented primary particles, a first shell portion formed on the first core portion and made of primary particles whose (001) planes are oriented in a direction from the center to the surface of the secondary particle, and a second shell portion formed on the first shell portion and made of randomly oriented primary particles.

[0022] According to the present invention, the first core portion of the positive electrode active material precursor is made of randomly oriented primary particles, the first shell portion is made of primary particles oriented in a direction from the center to the surface of the secondary particle, and the second shell portion is made of randomly oriented primary particles, and when the positive electrode active material is produced, the orientation of the positive electrode active material precursor is reflected in the positive electrode active material, thereby improving capacity characteristics, life characteristics, and resistance characteristics.

[0023] According to the present invention, the first core portion may have a composition represented by the following Chemical Formula 1.

[0024] [Chemical formula 1] [Ni a1 Co b1 Mn c1 M1 d1 M2 e1 ](OH)2

[0025] In the above Chemical Formula 1, M1 is one or more elements selected from Zr, B and Mg; M2 is one or more elements selected from Nb, Ti, Al, Mo, W, Ta, V and La; 0.6≦a1<1, 0 <b1≦0.4、0<c1≦0.4、0≦d1≦0.1、0≦e1≦0.1、a1+b1+c1+d1+e1=1である。

[0026] In the above Chemical Formula 1, M1 may be one or more elements selected from Zr and B, and M2 may be one or more elements selected from Nb and Ti.

[0027] The a1 means the atomic fraction of nickel among the metal elements in the first core portion, and may be 0.6≦a1<1, 0.6≦a1≦0.98, or 0.7≦a1≦0.95.

[0028] The b1 represents the atomic fraction of cobalt among the metal elements in the first core portion, and is 0 <b1≦0.4、0.01≦b1≦0.4、0.01≦b1≦0.3であることができる。

[0029] The c1 represents the atomic fraction of manganese among the metal elements in the first core portion, and is 0 <c1≦0.4、0.01≦c1≦0.4、0.01≦c1≦0.3であることができる。

[0030] The d1 means the atomic fraction of the M1 element among the metal elements in the first core portion, and may be 0≦d1≦0.1, 0≦d1≦0.05, or 0.001≦d1≦0.05.

[0031] The e1 represents the atomic fraction of the M2 element among the metal elements in the first core portion, and is 0 <e1≦0.1、0.01≦e1≦0.1、0.01≦e1≦0.05であることができる。

[0032] According to the present invention, the first shell portion may have a composition represented by the following Chemical Formula 2.

[0033] [Chemical formula 2] [Ni a2 Co b2 Mn c2 M1 d2 ](OH)2

[0034] In the above Chemical Formula 2, M1 is one or more elements selected from Zr, B and Mg; 0.6≦a2<1, 0 <b2≦0.4、0<c2≦0.4、0≦d2≦0.1、a2+b2+c2+d2=1である。

[0035] In the above Chemical Formula 2, M1 may be one or more elements selected from Zr and B.

[0036] The a2 means the atomic fraction of nickel among the metal elements in the first shell portion, and may be 0.6≦a2<1, 0.6≦a2≦0.98, or 0.7≦a2≦0.95.

[0037] The b2 represents the atomic fraction of cobalt among the metal elements in the first shell portion, and is 0 <b2≦0.4、0.01≦b2≦0.4、0.01≦b2≦0.3であることができる。

[0038] The c2 represents the atomic fraction of manganese among the metal elements in the first shell portion, and is 0 <c2≦0.4、0.01≦c2≦0.4、0.01≦c2≦0.3であることができる。

[0039] The d2 means the atomic fraction of the M1 element among the metal elements in the first shell portion, and may be 0≦d2≦0.1, 0≦d2≦0.05, or 0.001≦d2≦0.05.

[0040] According to the present invention, the second shell portion may have a composition represented by the following Chemical Formula 3.

[0041] [Chemical formula 3] [Ni a3 Co b3 Mn c3 M1 d3 M3 f3 ](OH)2

[0042] In the above Chemical Formula 3, M1 is one or more elements selected from Zr, B and Mg; M3 is one or more elements selected from Nb, Ti, Al, Mo, W, Ta, V and La; 0.6≦a3<1, 0 <b3≦0.4、0<c3≦0.4、0≦d3≦0.1、0<f3≦0.1、a3+b3+c3+d3+f3=1である。

[0043] In the above Chemical Formula 3, M1 may be one or more elements selected from Zr and B, and M3 may be Al.

[0044] The a3 means the atomic fraction of nickel among the metal elements in the second shell portion, and may be 0.6≦a3<1, 0.6≦a3≦0.98, or 0.7≦a3≦0.95.

[0045] The b3 represents the atomic fraction of cobalt among the metal elements in the second shell portion, and is 0 <b3≦0.4、0.01≦b3≦0.4、0.01≦b3≦0.3であることができる。

[0046] The c3 represents the atomic fraction of manganese among the metal elements in the second shell portion, and is 0 <c3≦0.4、0.01≦c3≦0.4、0.01≦c3≦0.3であることができる。

[0047] The d3 means the atomic fraction of the M1 element among the metal elements in the second shell portion, and may be 0≦d3≦0.1, 0≦d3≦0.05, or 0.001≦d3≦0.05.

[0048] The f3 represents the atomic fraction of the M3 element among the metal elements in the second shell portion, and is 0 <f3≦0.1、0.01≦f3≦0.1、0.01≦f3≦0.05であることができる。

[0049] Specifically, the positive electrode active material precursor may include a first core portion having a composition represented by Chemical Formula 1, a first shell portion formed on the first core portion and having a composition represented by Chemical Formula 2, and a second shell portion formed on the first shell portion and having a composition represented by Chemical Formula 3. Here, M1 may be an element that does not affect the orientation of primary particles contained in the positive electrode active material precursor, such as Zr or B, and M3 may be an element that eliminates the orientation of primary particles contained in the positive electrode active material precursor, such as Nb, Ti, Al, or Mo.

[0050] FIG. 1 is a schematic diagram of a cathode active material precursor according to the present invention. Referring to FIG. 1, it can be seen that the cathode active material precursor 100 according to the present invention has a structure of a first core portion 110, a first shell portion 120 and a second shell portion 130. The cathode active material precursor according to the present invention has a structure of a first core portion-a first shell portion-a second shell portion, and the first core portion, the first shell portion and the second shell portion each have [Ni a1 Co b1 Mn c1 M1 d1 M2 e1 ](OH)2,[Ni a2 Co b2 Mn c2 M1 d2 ](OH)2,[Ni a3 Co b3 Mn c3 M1 d3 M3 f3 Because the material has a composition of ](OH)2, side reactions between dopants are suppressed and the doping efficiency is increased, thereby realizing characteristics such as increased life or improved output, which are in line with the purpose of dopant selection, without compromising existing performance.

[0051] According to the present invention, the first shell portion may have a thickness of 1 μm to 9 μm, specifically 2 μm to 7 μm, more specifically 2 μm to 4 μm, In this case, when the positive electrode active material precursor is calcined to prepare the positive electrode active material, the proportion of primary particles that maintain a radial orientation of the (003) plane in the positive electrode active material can be increased, thereby improving the life characteristics and resistance characteristics.

[0052] According to the present invention, the second shell portion may have a thickness of 0.5 μm to 2 μm, specifically, 0.5 μm to 1.5 μm. In this case, when the positive electrode active material precursor is calcined to prepare the positive electrode active material, the average particle size (D 50 ) of 1 μm or less can be formed, and the capacitance and output characteristics can be improved.

[0053] The positive electrode active material precursor has an average particle size (D 50) can be 1 μm to 20 μm, specifically 4 μm to 18 μm, and more specifically 9 μm to 15 μm. When the average particle size of the positive electrode active material precursor is within the above range, the energy density of the battery is increased, and there is an advantageous effect on the life and output characteristics.

[0054] Method for producing a positive electrode active material precursor The positive electrode active material precursor according to the present invention may be manufactured by a method including the steps of: (A) continuously feeding a transition metal-containing solution containing nickel (Ni), cobalt (Co) and manganese (Mn) ions, an ammonium cation complexing agent and a basic solution into a reactor (optionally, a first doping solution containing M1 ions and / or a second doping solution containing M2 ions may be further fed) and conducting a coprecipitation reaction to form a first core portion; (B) continuously feeding the transition metal-containing solution, the ammonium cation complexing agent and a basic solution into a reactor containing the first core portion (optionally, the first doping solution containing M1 ions may be further fed) and conducting a coprecipitation reaction to form a first shell portion on the first core portion; and (C) continuously feeding the transition metal-containing solution, a third doping solution, an ammonium cation complexing agent and a basic solution into a reactor containing the first shell portion formed on the first core portion (optionally, the first doping solution containing M1 ions may be further fed) and conducting a coprecipitation reaction to form a second shell portion on the first shell portion. Here, the coprecipitation reaction in the step (B) may be carried out at a lower pH than the coprecipitation reaction in the step (A).

[0055] In the step (A), a first doping solution containing M1 (one or more elements selected from Zr, B, and Mg) ions, a second doping solution containing M2 (one or more elements selected from Nb, Ti, Al, Mo, W, Ta, V, and La) ions, or a combination thereof may be further added and co-precipitated to form a first core portion.

[0056] In the step (B), a first doping solution containing M1 (one or more elements selected from Zr, B, and Mg) ions may be further introduced to cause a coprecipitation reaction to form a first shell portion on the first core portion.

[0057] In the step (C), a first doping solution containing M1 (one or more elements selected from Zr, B, and Mg) ions may be further added to cause a coprecipitation reaction to form a second shell portion on the first shell portion.

[0058] According to the method for producing the positive electrode active material precursor, two or more doping elements can be doped in separate steps, so that two or more doping elements can be doped without decreasing the doping efficiency.

[0059] Meanwhile, M1 may be included in all of the first core portion, the first shell portion, and the second shell portion. In this case, without separately preparing the first doping solution, the M1 precursor material may be further added to the transition metal-containing solution, and then the transition metal-containing solution further containing M1 ions may be continuously added to a reactor to perform a co-precipitation reaction to prepare a cathode active material precursor. Here, the M1 precursor material may be one that is not reactive with the transition metal-containing solution. When M1 is zirconium, the M1 precursor material may be, for example, Zr(SO4)2, ZrCl4, Zr(CH 12 O8), etc. When M1 is boron, the M1 source material can be, for example, H3BO3, B2O3, BCl3, etc.

[0060] The transition metal-containing solution may include a nickel source material, a cobalt source material, and a manganese source material.

[0061] The nickel source material may be nickel-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or oxyhydroxide, etc., specifically, Ni(OH)2, NiO, NiOOH, NiCO3·2Ni(OH)2·4H2O, NiC2O2·2H2O, Ni(NO3)2·6H2O, NiSO4, NiSO4·6H2O, Ni(SO3)2, or combinations thereof, but is not limited thereto.

[0062] The cobalt source material may be a cobalt-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or oxyhydroxide, etc., specifically, Co(OH)2, CoOOH, Co(OCOCH3)2·4H2O, Co(NO3)2·6H2O, CoSO4, Co(SO4)2·7H2O, Co(SO3)2, or a combination thereof, but is not limited thereto.

[0063] The manganese-containing raw material may be manganese-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or oxyhydroxide, etc., specifically, Mn2O3, MnO2, Mn3O4, MnCO3, Mn(NO3)2, MnSO4, Mn(SO3)2, manganese acetate, manganese dicarboxylate, manganese citrate, fatty acid manganese salt, manganese oxyhydroxide, manganese chloride, or a combination thereof, but is not limited thereto.

[0064] The transition metal-containing solution may be prepared by adding a nickel-containing raw material, a cobalt-containing raw material, and a manganese-containing raw material to a solvent, specifically, water or a mixed solvent of an organic solvent (e.g., alcohol, etc.) that is uniformly miscible with water, but is not limited thereto. Meanwhile, when the transition metal-containing solution further contains ions of one or more elements selected from Zr, Al, W, Ti, Nb, Ta, V, Mo, and B, the transition metal-containing solution may be prepared by adding one or more element-containing raw materials selected from Zr, Al, W, Ti, Nb, Ta, V, Mo, and B to the solvent.

[0065] The first doping solution contains M1 (one or more elements selected from Zr, B, and Mg) ions. The first doping solution may be prepared by adding an M1-containing raw material (e.g., Zr(SO4)2, H3BO3, etc.) to a solvent, specifically, water, an organic solvent that can be uniformly mixed with water (e.g., alcohol, etc.), or a mixed solvent of a basic solvent such as an aqueous NaOH solution, but is not limited thereto.

[0066] The second doping solution contains M2 (one or more elements selected from Nb, Ti, Al, Mo, W, Ta, V, and La) ions, and the third doping solution contains M3 (one or more elements selected from Nb, Ti, Al, Mo, W, Ta, V, and La) ions. The second or third doping solution may be prepared by adding a raw material containing M2 or M3 (e.g., ammonium niobate oxalate, ammonium titanyl oxalate, Al(NO3)2, etc.) to a solvent, specifically, water, an organic solvent that can be uniformly mixed with water (e.g., alcohol, etc.), or a mixed solvent of a basic solvent such as an aqueous NaOH solution, but is not limited thereto.

[0067] The ammonium cation complexing agent may include, but is not limited to, for example, NH4OH, (NH4)2SO4, NH4NO3, NH4Cl, CH3COONH4, NH4CO3, or a combination thereof. Meanwhile, the ammonium cation complexing agent may be used in the form of an aqueous solution, and in this case, the solvent may be water or a mixture of water and an organic solvent (e.g., alcohol, etc.) that is uniformly miscible with water.

[0068] The basic solution may contain an alkali compound such as a hydroxide of an alkali metal or an alkaline earth metal, a hydrate thereof, or a combination thereof, such as NaOH, KOH, or Ca(OH)2, as a precipitant. The basic solution may also be used in the form of an aqueous solution, and the solvent may be water or a mixture of water and an organic solvent (e.g., alcohol, etc.) that is uniformly miscible with water.

[0069] The coprecipitation reactions in steps (A), (B) and (C) may be carried out under the following conditions, but are not limited thereto.

[0070] The coprecipitation reaction in step (A) can be carried out at a pH of 10 to 12.5, specifically at a pH of 11 to 12.5, and more specifically at a pH of 11.5 to 12.5. When the coprecipitation reaction in step (A) is carried out at a pH within the above range, the reactivity of the metal element with the -OH group can be promoted to form small and uniform cores.

[0071] The coprecipitation reaction in step (A) may be carried out at 40° C. to 60° C., specifically 50° C. to 58° C., and more specifically 50° C. to 55° C. When the coprecipitation reaction in step (A) is carried out at a temperature within the above range, the size and uniformity of the primary particles can be improved, and the yield can be increased.

[0072] The co-precipitation reaction in step (A) may be carried out for 0.5 to 20 hours, specifically 1 to 16 hours, and more specifically 1.5 to 16 hours. When the co-precipitation reaction in step (A) is carried out for a time within the above range, the surface energy can be lowered and the uniformity improved by a sufficient reaction time after the seed generation, and preparations can be made to move to the growth step.

[0073] The coprecipitation reaction in step (A) can be carried out in a non-oxidizing atmosphere, specifically, a nitrogen atmosphere, in which case oxidation of the precursor can be suppressed and a precursor with a uniform phase can be obtained.

[0074] The step (A) is a seed generating step, and the first core part manufactured by the step (A) is composed of randomly oriented primary particles. Meanwhile, in the seed generating step, a doping solution containing a doping element may be selectively added to improve the performance of the battery, and in the seed generating step, primary particles without orientation are formed regardless of the type of doping element.

[0075] The coprecipitation reaction in step (B) may be carried out at a pH of 10 to 11.8, specifically 10.5 to 11.6, and more specifically 11 to 11.4. When the coprecipitation reaction in step (B) is carried out at a pH lower than that of the coprecipitation reaction in step (A) and within the above range, the generation of seeds may be suppressed, and primary particles on the surface may grow from the previously formed seeds, so that the size of the precursor particles may gradually increase. If the pH is too high, the surface of the primary particles may be formed as coalescence rather than oriented growth, and polycrystallinity may increase during sintering for the production of the positive electrode active material, forming many grains and defects in the primary particles, which may reduce the life characteristics.

[0076] The coprecipitation reaction in step (B) may be carried out at 40° C. to 60° C., specifically 50° C. to 58° C., and more specifically 50° C. to 55° C. When the coprecipitation reaction in step (B) is carried out at a temperature within the above range, it has the effect of suppressing the generation of additional particles and inducing uniform growth of particles.

[0077] The coprecipitation reaction in step (B) may be carried out for 10 to 100 hours, specifically 20 to 80 hours, and more specifically 30 to 64 hours. When the coprecipitation reaction in step (B) is carried out for a time within the above range, the sphericity of the particles increases and the size distribution narrows, so that uniform primary particles can be formed.

[0078] The coprecipitation reaction in step (B) can be carried out in a non-oxidizing atmosphere, specifically, a nitrogen atmosphere, in which case the precursor phase can be uniformly formed to make the reactivity with lithium uniform and defects in the primary particles can be suppressed.

[0079] The step (B) is a particle growth step, and the primary particles forming the first shell portion produced by the step (B) may have a specific orientation. Specifically, primary particles may be produced in which the (001) plane is oriented in a direction from the center of the secondary particle to the surface. In the step (B), in order to improve the performance of the battery, a first doping solution containing a doping element (one or more elements selected from Zr, B, and Mg) that does not eliminate the orientation of the primary particles (does not affect the orientation of the primary particles) may be selectively added.

[0080] The coprecipitation reaction in step (C) may be carried out at a pH of 10 to 11.8, specifically, at a pH of 10.5 to 11.6, and more specifically, at a pH of 10.8 to 11.2. When the coprecipitation reaction in step (C) is carried out at a pH within the above range, the addition of the wet dopant suppresses side reactions that may occur due to the difference in reactivity with existing metal ions, and has an advantageous effect of uniformly doping the doping element on the surface.

[0081] The coprecipitation reaction in step (C) may be carried out at 40° C. to 60° C., specifically 50° C. to 58° C., and more specifically 50° C. to 55° C. When the coprecipitation reaction in step (C) is carried out at a temperature within the above range, it has the effect of suppressing the generation of additional particles and inducing uniform growth of particles.

[0082] The coprecipitation reaction in step (C) may be carried out for 2 hours to 48 hours, specifically 4 hours to 40 hours, and more specifically 8 hours to 32 hours. When the coprecipitation reaction in step (C) is carried out for a time within the above range, the thickness of the primary particles gradually decreases during step (C) and the growth direction of the primary particles is randomly formed, thereby increasing the BET of the surface of the positive electrode active material produced when the positive electrode active material precursor is calcined.

[0083] The coprecipitation reaction in step (C) can be carried out in a non-oxidizing atmosphere, specifically, a nitrogen atmosphere, in which case the precursor phase can be uniformly formed to make the reactivity with lithium uniform and defects in the primary particles can be suppressed.

[0084] The step (C) is also a particle growth step, but since a third doping solution containing a doping element (one or more elements selected from Nb, Ti, Al, Mo, W, Ta, V, and La) that causes the primary particles to lose their orientation is required in the step (C), the primary particles forming the second shell portion produced by the step (C) do not have orientation.

[0085] positive electrode active material The positive electrode active material according to the present invention is a spherical secondary particle formed by aggregation of primary particles, and includes a second core portion made of randomly oriented primary particles, a third shell portion formed on the second core portion and made of rod-shaped primary particles whose (003) planes are oriented in a direction from the center to the surface of the secondary particle, and a fourth shell portion formed on the third shell portion and made of randomly oriented primary particles.

[0086] 2, which is a schematic diagram of a positive electrode active material according to the present invention, the positive electrode active material 200 may include a second core portion 210 made of randomly oriented primary particles, a third shell portion 220 made of rod-shaped primary particles whose (003) planes are oriented in a direction from the center to the surface of the secondary particles, and a fourth shell portion 230 made of randomly oriented primary particles. In this case, the rod-shaped primary particles are formed in a specific orientation in the third shell portion, which is the middle layer, and the migration path during liquid diffusion outside the lithium primary particles can be minimized, thereby improving output characteristics.

[0087] According to the present invention, the primary particles forming the second core portion may be spherical primary particles. Also, the primary particles forming the fourth shell portion may be spherical primary particles. The positive electrode active material is manufactured from the positive electrode active material precursor according to the present invention, and has a form of the second core portion-the third shell portion-the fourth shell portion, and the second core portion, the third shell portion and the fourth shell portion have a uniform composition (even if the positive electrode active material precursor has different compositions of the first core portion, the first shell portion and the second shell portion, the composition becomes uniform by firing at a high temperature for a long period of time), and the second core portion may be composed of randomly oriented spherical primary particles, the third shell portion may be composed of rod-shaped primary particles whose (003) plane is oriented in a direction from the center of the secondary particle to the surface, and the fourth shell portion may be composed of randomly oriented spherical primary particles.

[0088] According to the present invention, the positive electrode active material may have a composition represented by the following Chemical Formula 4.

[0089] [Chemical formula 4] Li x [Ni a4 Co b4 Mn c4 M1 d4 M2 e4 M3 f4 ]O2

[0090] In the above Chemical Formula 4, M1 is one or more elements selected from Zr, B and Mg; M2 and M3 are each independently one or more elements selected from Nb, Ti, Al, Mo, W, Ta, V, and La; 0.9≦x≦1.2, 0.6≦a4<1, 0 <b4≦0.4、0<c4≦0.4、0≦d4≦0.1、0≦e4≦0.1、0<f4≦0.1、a4+b4+c4+d4+e4+f4=1である。

[0091] According to the present invention, the third shell portion may have a thickness of 1 μm to 9 μm, specifically 2 μm to 7 μm, and more specifically 2 μm to 5 μm. In this case, the ratio of primary particles having a radial orientation of the (003) plane is high, and the life characteristics and resistance characteristics can be improved.

[0092] According to the present invention, the fourth shell portion may have a thickness of 0.5 μm to 2 μm, specifically 0.5 μm to 1.5 μm, and more specifically 0.5 μm to 1 μm, which increases the specific surface area of ​​the positive electrode active material and improves the capacity and output characteristics.

[0093] The positive electrode active material has an average particle size (D 50 ) can be 1 μm to 20 μm, specifically 4 μm to 18 μm, and more specifically 9 μm to 15 μm. When the average particle size of the positive electrode active material is within the above range, the energy density of the battery is increased, and there is an advantageous effect on the life and output characteristics.

[0094] Method for producing positive electrode active material The cathode active material according to the present invention may be prepared, for example, by a method including a step of mixing the cathode active material precursor according to the present invention with a lithium-containing raw material and heat-treating the mixture to form a lithium transition metal oxide, but is not limited thereto.

[0095] The lithium-containing raw material may be lithium-containing sulfate, nitrate, acetate, carbonate, oxalate, citrate, halide, hydroxide, oxyhydroxide, etc. The lithium-containing raw material may be specifically lithium hydroxide hydrate, more specifically LiOH·H2O. In this case, the reactivity of the lithium-containing raw material with a precursor having a high atomic fraction of nickel among the metal elements in the precursor may be improved.

[0096] When preparing the positive electrode active material, the positive electrode active material precursor and the lithium-containing raw material may be mixed in a molar ratio of 1:1 to 1:1.1, preferably 1:02 to 1:07, and more preferably 1:05 to 1:1.07. If the lithium-containing raw material is mixed in an amount less than this range, the capacity of the positive electrode active material may decrease, and if the lithium-containing raw material is mixed in an amount exceeding this range, unreacted Li may remain as a by-product, resulting in a decrease in capacity and separation of the positive electrode active material particles after firing (induction of a coalescence phenomenon of the positive electrode active material).

[0097] The heat treatment temperature can be 700° C. to 850° C., specifically 750° C. to 830° C., and more specifically 760° C. to 810° C. When the heat treatment temperature is within the above range, the size of the primary particles can be controlled, and the life and output characteristics can be improved.

[0098] The heat treatment can be carried out in an oxygen atmosphere, which can increase the reactivity of lithium with the precursor, suppress the formation of unnecessary phases, and reduce cation mixing.

[0099] The heat treatment can be carried out for 5 to 30 hours. The heat treatment can be carried out for preferably 8 to 20 hours, more preferably 8 to 15 hours. When the heat treatment time is within the above range, a layered structure can be formed uniformly, and the generation of a spinel structure or rock salt structure can be suppressed, thereby reducing the residual lithium value.

[0100] positive electrode The present invention also provides a positive electrode for a lithium secondary battery, which contains the positive electrode active material produced by the above-mentioned method.

[0101] Specifically, the positive electrode includes a positive electrode current collector and a positive electrode active material layer located on at least one surface of the positive electrode current collector and including the positive electrode active material.

[0102] The positive electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode current collector can usually have a thickness of 3 μm to 500 μm, and fine irregularities can be formed on the surface of the current collector to increase the adhesive force of the positive electrode active material. For example, it can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0103] The positive electrode active material layer may contain a conductive material and a binder in addition to the positive electrode active material.

[0104] The positive electrode active material may be included in an amount of 80 wt% to 99 wt%, more specifically, 85 wt% to 98 wt%, based on the total weight of the positive electrode active material layer, and excellent capacity characteristics may be exhibited when included in the above content range.

[0105] The conductive material is used to give conductivity to the electrode, and can be used without any particular limitation as long as it does not cause a chemical change in the battery and has electronic conductivity. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and among these, one type alone or a mixture of two or more types can be used. The conductive material can be contained in an amount of 1% by weight to 30% by weight based on the total weight of the positive electrode active material layer.

[0106] The binder serves to improve adhesion between the positive electrode active material particles and adhesion between the positive electrode active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one or more of these may be used alone or in combination. The binder may be included in an amount of 1 wt% to 30 wt% based on the total weight of the positive electrode active material layer.

[0107] The positive electrode may be manufactured by a typical method for manufacturing a positive electrode, except for using the positive electrode active material. Specifically, the positive electrode may be manufactured by applying a composition for forming a positive electrode active material layer, which is prepared by dissolving or dispersing the positive electrode active material and, optionally, a binder and a conductive material in a solvent, onto a positive electrode current collector, followed by drying and rolling. In this case, the types and contents of the positive electrode active material, binder, and conductive material are as described above.

[0108] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and may be used alone or in combination of two or more of these. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, and to provide a viscosity that allows excellent thickness uniformity during subsequent coating for the manufacture of a positive electrode, taking into consideration the coating thickness of the slurry and the manufacturing yield.

[0109] As another method, the positive electrode can also be produced by casting the composition for forming a positive electrode active material layer on another support, peeling the composition from the support, and laminating the resulting film on a positive electrode current collector.

[0110] Lithium secondary battery In addition, the present invention can provide an electrochemical device including the positive electrode. The electrochemical device can be, for example, a battery or a capacitor, and more specifically, a lithium secondary battery.

[0111] Specifically, the lithium secondary battery includes a positive electrode, a negative electrode facing the positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte. Since the positive electrode is as described above, a detailed description thereof will be omitted, and only the remaining components will be described in detail below.

[0112] Also, the lithium secondary battery may optionally further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.

[0113] In the lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0114] The negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may have a thickness of usually 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0115] The negative electrode active material layer includes a negative electrode active material, and optionally a binder and a conductive material.

[0116] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β(0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites and Sn-C composites, and any one or a mixture of two or more of these may be used. In addition, a metallic lithium thin film may be used as the negative electrode active material. In addition, both low crystalline carbon and high crystalline carbon may be used as the carbon material. Representative examples of low crystalline carbon include soft carbon and hard carbon, and representative examples of high crystalline carbon include amorphous, plate-like, flake-like, spherical or fibrous natural or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, mesocarbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes.

[0117] The negative electrode active material may be included in an amount of 80% by weight to 99% by weight based on the total weight of the negative electrode active material layer.

[0118] The binder is a component that facilitates bonding between the conductive material, the active material, and the current collector, and may be added in an amount of 0.1% by weight to 10% by weight based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.

[0119] The conductive material is a component for further improving the conductivity of the negative electrode active material, and may be added in an amount of 10% by weight or less, specifically 5% by weight or less, based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and examples of such conductive materials include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.

[0120] For example, the negative electrode active material layer can be produced by applying a negative electrode mixture, which is prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent, onto a negative electrode current collector and drying the applied material; alternatively, the negative electrode mixture can be cast onto another support, and then peeled off from the support to obtain a film, which can be laminated onto the negative electrode current collector.

[0121] For example, the negative electrode active material layer may be prepared by coating a negative electrode mixture prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material in a solvent, on a negative electrode current collector and drying the coated negative electrode mixture, or by casting the negative electrode mixture on a separate support and then peeling the negative electrode mixture from the support to obtain a film, which is then laminated on the negative electrode current collector.

[0122] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is generally used as a separator in a lithium secondary battery can be used without any particular limitation. In particular, a separator that has low resistance to ion movement of the electrolyte and has excellent electrolyte humidification ability is preferable. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof can be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high-melting point glass fiber, a polyethylene terephthalate fiber, etc. can be used. In addition, a separator coated with a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and can be selectively used as a single layer or a multilayer structure.

[0123] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.

[0124] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0125] The organic solvent may be any solvent that can act as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone; an ether solvent such as dibutyl ether or tetrahydrofuran; a ketone solvent such as cyclohexanone; an aromatic hydrocarbon solvent such as benzene or fluorobenzene; dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Examples of the solvents that can be used include carbonate-based solvents such as ethylene carbonate (PC), alcohol-based solvents such as ethyl alcohol and isopropyl alcohol, nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can enhance the charge / discharge performance of the battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred. In this case, the cyclic carbonate and the linear carbonate are mixed in a volume ratio of about 1:1 to about 1:9, so that the electrolyte can exhibit excellent performance.

[0126] The lithium salt can be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, the lithium salt can be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The lithium salt is preferably used within a concentration range of 0.1M to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, so that it can exhibit excellent electrolyte performance and lithium ions can move effectively.

[0127] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, in order to improve the life characteristics of the battery, suppress the decrease in the capacity of the battery, and improve the discharge capacity of the battery. In this case, the additives may be contained in an amount of 0.1% by weight to 5% by weight based on the total weight of the electrolyte.

[0128] As described above, the lithium secondary battery including the positive electrode active material according to the present invention stably exhibits excellent discharge capacity, output characteristics and life characteristics, and is therefore useful in portable devices such as mobile phones, notebook computers and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).

[0129] Therefore, according to another embodiment of the present invention, there is provided a battery module including the lithium secondary battery as a unit cell, and a battery pack including the same.

[0130] The battery module or battery pack may be used as a power source for one or more medium- to large-sized devices, such as a power tool; an electric vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV); or a power storage system.

[0131] The external shape of the lithium secondary battery of the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, or the like.

[0132] The lithium secondary battery according to the present invention can be used not only as a battery cell used as a power source for a small device, but also as a unit battery for a medium- to large-sized battery module including a large number of battery cells.

[0133] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to exemplary embodiments thereof, so that those skilled in the art can easily practice the present invention. However, the present invention may be embodied in many different forms and should not be construed as limited to the embodiments set forth herein.

[0134] Examples and Comparative Examples Example 1 NiSO4, CoSO4, and MnSO4 were dissolved in deionized water in amounts such that the molar ratio of Ni:Co:Mn was 88:5:7 to prepare a transition metal-containing solution with a concentration of 2.4 M. Zr(SO4)2 1500 ppm and H3BO3 (boric acid) 1120 ppm were further dissolved in the solution.

[0135] Ammonium niobate oxalate was dissolved in deionized water to prepare a second doping solution with a concentration of 1.2M.

[0136] The third doping solution was prepared by dissolving Al(NO3)3 in deionized water to a concentration of 1.2 M.

[0137] Deionized water was poured into a batch reactor (4.5 L), and nitrogen gas was purged into the reactor to remove dissolved oxygen in the water and create a non-oxidizing atmosphere in the reactor. Next, 15 wt% NaOH was poured in to maintain the pH in the reactor at 12.1. Next, 450 g of 9 wt% NH4OH was poured in.

[0138] The reactor was charged with 500 mL / h of the transition metal-containing solution further containing 1500 ppm Zr(SO4)2 and 1120 ppm H3BO3 (boric acid), 25 mL / h of the second doping solution, and 150 mL / h of 9 wt% NH4OH, respectively, and the reaction was carried out for 4 hours under conditions of a non-oxidizing atmosphere, pH 11.7 (adjusted by adding 15 wt% NaOH), a reaction temperature of 55°C, and a stirring speed of 650 rpm. 0.849 Co 0.048 Mn 0.068 Nb 0.024 B 0.01 Zr 0.001 The first core part (average particle size (D 50 ):3.2 μm) was formed.

[0139] The introduction of the second doping solution was stopped, and the transition metal-containing solution containing 1500 ppm Zr(SO4)2 and 1120 ppm H3BO3 (boric acid) was further dissolved at 500 mL / h and 150 mL / h of 9 wt% NH4OH was introduced into the reactor. The reaction was continued for 8 hours under conditions of pH 11.4 (adjusted by adding 15 wt% NaOH), reaction temperature 55°C, and stirring speed 450 rpm in a non-oxidizing atmosphere, to form Ni on the first core part. 0.87 Co 0.049 Mn 0.069 B 0.01 Zr 0.002A first shell portion (thickness: 2.5 μm) represented by (OH)2 was formed.

[0140] The reactor was charged with 500 mL / h of the transition metal-containing solution further containing 1500 ppm Zr(SO4)2 and 1120 ppm H3BO3 (boric acid), 50 mL / h of the third doping solution, and 150 mL / h of 9 wt% NH4OH, respectively, and the reaction was carried out for 8 hours under conditions of a non-oxidizing atmosphere, pH 11.0 (adjusted by adding 15 wt% NaOH), a reaction temperature of 55°C, and a stirring speed of 350 rpm, to form Ni on the first shell. 0.829 Co 0.047 Mn 0.066 Al 0.047 B 0.009 Zr 0.002 A second shell portion (thickness: 1 μm) represented by (OH) 2 was formed to produce a positive electrode active material precursor.

[0141] The positive electrode active material precursor and LiOH were mixed so that the molar ratio of Li:transition metal was 1.07:1, and the mixture was heat-treated at 805° C. for 20 hours to obtain a composition of LiNi 0.849 Co 0.048 Mn 0.068 Al 0.019 B 0.01 Nb 0.005 Zr 0.001 A positive electrode active material, O2, was produced.

[0142] Example 2 NiSO4, CoSO4 and MnSO4 were dissolved in deionized water in amounts such that the molar ratio of Ni:Co:Mn was 88:5:7 to prepare a transition metal-containing solution with a concentration of 2.4 M. Zr(SO4)2 (1500 ppm) was further dissolved in the solution.

[0143] Ammonium niobate oxalate was dissolved in deionized water to prepare a second doping solution with a concentration of 1.2M.

[0144] The third doping solution was prepared by dissolving Al(NO3)3 in deionized water to a concentration of 1.2 M.

[0145] Deionized water was poured into a batch reactor (4.5 L), and nitrogen gas was purged into the reactor to remove dissolved oxygen in the water and create a non-oxidizing atmosphere in the reactor. Next, 15 wt% NaOH was poured in to maintain the pH in the reactor at 12.1. Next, 450 g of 9 wt% NH4OH was poured in.

[0146] The reactor was charged with 500 mL / h of the transition metal-containing solution further containing 1500 ppm of Zr(SO4)2 dissolved therein, 25 mL / h of the second doping solution, and 150 mL / h of 9 wt% NH4OH, while reacting for 4 hours under conditions of a non-oxidizing atmosphere, pH 11.7 (adjusted by adding 15 wt% NaOH), a reaction temperature of 55°C, and a stirring speed of 650 rpm. 0.857 Co 0.049 Mn 0.068 Nb 0.024 Zr 0.002 The first core part (average particle size (D 50 ):3.2 μm) was formed.

[0147] The introduction of the second doping solution was stopped, and the transition metal-containing solution containing 1500 ppm of Zr(SO4)2 dissolved therein was introduced into the reactor at 500 mL / h, and 150 mL / h of 9 wt% NH4OH was introduced into the reactor. The reaction was continued for 8 hours under conditions of a non-oxidizing atmosphere, pH 11.4 (adjusted by introducing 15 wt% NaOH), a reaction temperature of 55°C, and a stirring speed of 450 rpm, to form Ni on the first core part. 0.879 Co 0.050 Mn 0.070 Zr 0.001 A first shell portion (thickness: 2.5 μm) represented by (OH)2 was formed.

[0148] The transition metal-containing solution further containing 1500 ppm of Zr(SO4)2 dissolved therein, 500 mL / h of the third doping solution, and 150 mL / h of 9 wt% NH4OH were respectively fed into the reactor, and the reaction was carried out for 8 hours under conditions of a non-oxidizing atmosphere, pH 11.0 (adjusted by feeding 15 wt% NaOH), a reaction temperature of 55°C, and a stirring speed of 350 rpm. 0.836 Co 0.048 Mn0.067 Al 0.048 Zr 0.001 A second shell portion (thickness: 1 μm) represented by (OH) 2 was formed to produce a positive electrode active material precursor.

[0149] The positive electrode active material precursor and LiOH were mixed so that the molar ratio of Li:transition metal was 1.07:1, and the mixture was heat-treated at 805° C. for 20 hours to obtain a composition of LiNi 0.857 Co 0.049 Mn 0.068 Al 0.019 Nb 0.005 Zr 0.001 A positive electrode active material, O2, was produced.

[0150] Example 3 NiSO4, CoSO4 and MnSO4 were dissolved in deionized water in amounts such that the molar ratio of Ni:Co:Mn was 88:5:7 to prepare a transition metal-containing solution with a concentration of 2.4 M. Zr(SO4)2 (1500 ppm) was further dissolved in the solution.

[0151] Ammonium niobate oxalate and ammonium titanyl oxalate were dissolved in deionized water in a molar ratio of 5:1.5 to prepare a second doping solution having a concentration of 1.2M.

[0152] The third doping solution was prepared by dissolving Al(NO3)3 in deionized water to a concentration of 1.2 M.

[0153] Deionized water was poured into a batch reactor (4.5 L), and nitrogen gas was purged into the reactor to remove dissolved oxygen in the water and create a non-oxidizing atmosphere in the reactor. Next, 15 wt% NaOH was poured in to maintain the pH in the reactor at 12.1. Next, 450 g of 9 wt% NH4OH was poured in.

[0154] The reactor was charged with 500 mL / h of the transition metal-containing solution further containing 1500 ppm of Zr(SO4)2 dissolved therein, 25 mL / h of the second doping solution, and 150 mL / h of 9 wt% NH4OH, while reacting for 4 hours under conditions of a non-oxidizing atmosphere, pH 11.7 (adjusted by adding 15 wt% NaOH), a reaction temperature of 55°C, and a stirring speed of 650 rpm. 0.851 Co 0.048 Mn 0.068 Nb 0.024 Ti 0.007 Zr 0.002 The first core part (average particle size (D 50 ):3.2 μm) was formed.

[0155] The supply of the second doping solution was stopped, and the transition metal-containing solution containing 1500 ppm of Zr(SO4)2 was further dissolved therein at 500 mL / h, and 150 mL / h of 9 wt% NH4OH was added to the reactor. The reaction was continued for 8 hours under conditions of pH 11.4 (adjusted by adding 15 wt% NaOH), reaction temperature 55°C, and stirring speed 450 rpm in a non-oxidizing atmosphere, to form Ni on the first core part. 0.879 Co 0.050 Mn 0.070 Zr 0.001 A first shell portion (thickness: 2.5 μm) represented by (OH)2 was formed.

[0156] The transition metal-containing solution further containing 1500 ppm of Zr(SO4)2 dissolved therein, 500 mL / h of the third doping solution, and 150 mL / h of 9 wt% NH4OH were respectively fed into the reactor, and the reaction was carried out for 8 hours under conditions of a non-oxidizing atmosphere, pH 11.0 (adjusted by feeding 15 wt% NaOH), a reaction temperature of 55°C, and a stirring speed of 350 rpm. 0.836 Co 0.048 Mn0 .067 Al 0.048 Zr 0.001 A second shell portion (thickness: 1 μm) represented by (OH) 2 was formed to produce a positive electrode active material precursor.

[0157] The positive electrode active material precursor and LiOH were mixed so that the molar ratio of Li:transition metal was 1.07:1, and the mixture was heat-treated at 805° C. for 20 hours to obtain a composition of LiNi 0.0856 Co 0.049 Mn 0.068 Al 0.019 Nb 0.005 Ti 0.001 Zr 0.001 A positive electrode active material, O2, was produced.

[0158] Comparative Example 1 After adding 4 L of distilled water to a batch reactor (20 L), the temperature was maintained at 58°C, and a transition metal aqueous solution with a concentration of 2.29 mol / L, which was a mixture of NiSO4, CoSO4, and MnSO4 so that the molar ratio of nickel:cobalt:manganese was 88:5:7, was added to the reactor at 510 mL / hr, and a 9 wt% aqueous ammonia solution was continuously added to the reactor at 510 mL / hr. Then, a 15 wt% aqueous sodium hydroxide solution was added at 306 mL / hr, and the sodium hydroxide aqueous solution was added at a rate adjusted to maintain the pH at 11.4.

[0159] Nucleation was performed for the first 30 minutes by stirring at 600 rpm, and thereafter, particle growth was performed with stirring at 250-600 rpm. After 20 hours of coprecipitation reaction, when the inside of the batch reactor was filled to a certain extent, stirring was stopped and the precursor particles were allowed to settle, and the supernatant liquid was removed leaving 4 L of reactant, and the reaction was continued again. The reaction was continued for a total of 40 hours to form precursor particles.

[0160] The above-prepared positive electrode active material precursor, LiOH, and doping elements Al, B, Nb, and Zr were mixed in a molar ratio of 1:1.07:0.02:0.01:0.005:0.0015, and sintered at 770°C for 10 hours in an oxygen atmosphere to obtain a dry NCMA positive electrode active material doped with Al, B, Nb, and Zr (composition: LiNi 0.849 Co 0.048 Mn 0.068 Al 0.019 B 0.01 Nb 0.005 Zr 0.001 O2) was manufactured.

[0161] Comparative Example 2 NiSO4, CoSO4, and MnSO4 were dissolved in deionized water in amounts such that the molar ratio of Ni:Co:Mn was 88:5:7 to prepare a transition metal-containing solution with a concentration of 2.4 M. Zr(SO4)2 1500 ppm and H3BO3 (boric acid) 1120 ppm were further dissolved in the solution.

[0162] Ammonium niobate oxalate was dissolved in deionized water to prepare a second doping solution with a concentration of 1.2M.

[0163] The third doping solution was prepared by dissolving Al(NO3)3 in deionized water to a concentration of 1.2 M.

[0164] Deionized water was poured into a batch reactor (4.5 L), and nitrogen gas was purged into the reactor to remove dissolved oxygen in the water and create a non-oxidizing atmosphere in the reactor. Next, 15 wt% NaOH was poured in to maintain the pH in the reactor at 12.1. Next, 450 g of 9 wt% NH4OH was poured in.

[0165] The reactor was charged with 500 mL / h of the transition metal-containing solution further containing 1500 ppm of Zr(SO4)2 dissolved therein, 5 mL / h of the second doping solution, 40 mL / h of the third doping solution, and 150 mL / h of 9 wt% NH4OH, respectively, and the reaction was carried out for 4 hours under conditions of a non-oxidizing atmosphere, pH 11.7 (adjusted by adding 15 wt% NaOH), a reaction temperature of 55°C, and a stirring speed of 650 rpm. 0.854 Co 0.05 Mn 0.07 Al 0.02 Nb 0.005 B 0.01 Zr 0.002 A core portion represented by (OH)2 was formed.

[0166] After adjusting the pH to 11.4 by adding 15 wt% NaOH, 500 mL / h of the transition metal-containing solution further containing 1500 ppm of Zr(SO4)2, 5 mL / h of the second doping solution, 40 mL / h of the third doping solution, and 150 mL / h of 9 wt% NH4OH were added to the reactor, and the reaction was carried out for 16 hours under conditions of pH 11.4, reaction temperature 55°C, and stirring speed 450 rpm in a non-oxidizing atmosphere, resulting in the formation of Ni on the core part. 0.854 Co 0.05 Mn 0.07 Al 0.02 Nb 0.005 B 0.01 Zr 0.002 A first shell portion represented by (OH)2 was formed to produce a positive electrode active material precursor.

[0167] The positive electrode active material precursor and LiOH were mixed so that the molar ratio of Li:transition metal was 1.07:1, and the mixture was heat-treated at 805° C. for 20 hours to obtain a composition of LiNi 0.849 Co 0.048 Mn 0.068 Al 0.019 B 0.01 Nb 0.005 Zr 0.001 A positive electrode active material, O2, was produced.

[0168] Experimental Example Experimental Example 1: Analysis of Positive Electrode Active Material Precursor and Positive Electrode Active Material A SEM image of a cross section of the positive electrode active material precursor of Example 1 and a TEM image of the first shell portion were measured and are shown in FIG. 3. A SEM image of a cross section of the positive electrode active material precursor of Example 1 and TEM images of the third and fourth shell portions were measured and are shown in FIG. 4.

[0169] In addition, SEM images of the positive electrode active material precursor and the positive electrode active material of each of Examples 1 to 3 and Comparative Examples 1 and 2 were measured and are shown in Figures 5 to 9. In Figures 5 to 7, (A) is an SEM image of the positive electrode active material precursor, and (B) is an SEM image of the positive electrode active material. In Figures 8 and 9, (A) is an SEM image of the positive electrode active material precursor, (B) is a cross-section of the positive electrode active material precursor, (C) is a positive electrode active material, and (D) is an SEM image of a cross-section of the positive electrode active material.

[0170] 3, 5(A), 6(A) and 7(A), the precursors of Examples 1 to 3 are spherical secondary particles formed by agglomeration of primary particles, and include a first core part made of randomly oriented primary particles, a first shell part formed on the first core part and made of primary particles with the (001) plane oriented in a direction from the center of the secondary particle to the surface, and a second shell part formed on the first shell part and made of randomly oriented primary particles. Also, with reference to FIG. 4, 5(B), 6(B) and 7(B), the positive electrode active material of Examples 1 to 3 is spherical secondary particles formed by agglomeration of primary particles, and includes a second core part made of randomly oriented primary particles, a third shell part formed on the second core part and made of rod-shaped primary particles with the (003) plane oriented in a direction from the center of the secondary particle to the surface, and a fourth shell part formed on the third shell part and made of randomly oriented primary particles.

[0171] Experimental example 2: Evaluation of capacitance and resistance characteristics Lithium secondary batteries were produced using the positive electrode active materials produced in Examples 1 to 3 and Comparative Examples 1 and 2, and the initial charge capacity, initial discharge capacity, capacity retention rate, and resistance increase rate were evaluated for each of the lithium secondary batteries.

[0172] The positive electrode active material prepared in each of Examples 1 to 3 and Comparative Examples 1 and 2, conductive material (FX35), and binder (PVDF) were mixed in a weight ratio of 97.5:1:1.5 in N-methyl-2-pyrrolidone (NMP) solvent to prepare a positive electrode slurry. The positive electrode slurry was applied to one side of an aluminum current collector, dried, and rolled to prepare a positive electrode. Then, the negative electrode active material (artificial graphite), conductive material (Super C-65), and binder (BM-L302) were mixed in a ratio of 95.6:2.1:2.3 in water (H2O) to prepare a negative electrode slurry. The negative electrode slurry was applied to one side of a copper current collector, dried, and rolled to prepare a negative electrode. A separator was interposed between the positive electrode and the negative electrode to prepare an electrode assembly, which was then placed inside a battery case and an electrolyte was injected to prepare a lithium secondary battery. The electrolyte used here was prepared by dissolving 1M LiPF6 in an organic solvent in which ethylene carbonate:ethyl methyl carbonate was mixed at a volume ratio of 3:7.

[0173] Then, the secondary batteries were charged at a constant current of 0.1 C to 4.25 V at 25° C. Then, they were discharged at a constant current of 0.1 C to 3 V to measure the initial charge capacity and the initial discharge capacity. The results are shown in Table 1 below.

[0174] Then, charge / discharge cycles were repeated 30 times at a constant current of 0.33 C in the range of 3.0 to 4.25 V at 45° C., and the capacity of the lithium secondary battery was measured, and in particular, the ratio of the discharge capacity at the 30th cycle to the discharge capacity at the first cycle was taken as the capacity retention rate, which is shown in Table 1 below. In addition, the ratio of DCIR obtained by dividing the voltage drop (ΔV) for 60 seconds in the 30th discharge cycle by the current to DCIR obtained by dividing the voltage drop (ΔV) for 60 seconds in the first discharge cycle by the current was taken as the resistance increase rate, which is shown in Table 1 below.

[0175] [Table 1]

[0176] Referring to Table 1, it can be seen that the positive electrode active materials of Examples 1 to 3 have superior initial discharge capacity, superior capacity retention rate, and smaller initial resistance as well as a smaller resistance increase rate compared to the positive electrode active materials of Comparative Examples 1 and 2.

[0177] As a result, the positive electrode active material according to the present invention is prepared from a positive electrode active material precursor including a first core portion made of randomly oriented primary particles, a first shell portion formed on the first core portion and made of primary particles with the (001) plane oriented in a direction from the center of the secondary particle toward the surface, and a second shell portion formed on the first shell portion and made of randomly oriented primary particles, and the orientation of the first shell portion of the positive electrode active material precursor remains in the positive electrode active material, and it is found that the positive electrode active material has excellent capacity characteristics, life characteristics, and resistance characteristics. In particular, since the positive electrode active material precursor has a first core portion-first shell portion-second shell portion form and the first core portion, first shell portion, and second shell portion each have a specific composition, it is found that side reactions between dopants are suppressed and doping efficiency is increased, and characteristics such as increased life or improved output, which are in line with the purpose of dopant selection, can be realized without deteriorating existing performance.

[0178] In contrast, the positive electrode active material precursor and positive electrode active material of Comparative Example 1 are different in form from the positive electrode active material precursor and positive electrode active material of the present invention in that they do not include two shell layers with different primary particle orientations, and it can be confirmed that Comparative Example 1 uses various doping elements simultaneously during dry doping, and undesirable substances are generated on the surface of the positive electrode active material due to side reactions between the doping elements, resulting in problems with capacity, life, and resistance characteristics. Also, the positive electrode active material precursor and positive electrode active material of Comparative Example 2 are different in form from the positive electrode active material precursor and positive electrode active material of the present invention in that they do not include two shell layers with different primary particle orientations, and it can be confirmed that Comparative Example 1 uses various doping elements simultaneously during wet doping, and the doping elements change the surface energy, causing changes in the shape, size, orientation, etc. of the primary particles, resulting in problems with capacity, life, and resistance characteristics. [Explanation of symbols]

[0179] 100 Positive electrode active material precursor 110 First Core Section 120 First Shell Part 130 Second Shell Part 200 Cathode active material 210 Second Core Section 220 3rd Shell Section 230 4th Shell Section

Claims

1. They are spherical secondary particles formed by agglomeration of primary particles, a first core portion made of randomly oriented primary particles, a first shell portion formed on the first core portion and made of primary particles whose (001) planes are oriented in a direction from the center of the secondary particle toward a surface, and a second shell portion formed on the first shell portion and made of randomly oriented primary particles, The first core portion has a composition represented by the following chemical formula 1: [Chemical formula 1] [Ni a1 Co b1 Mn c1 M1 d1 M2 e1 ] (OH) 2 In the above Chemical Formula 1, M1 is one or more elements selected from Zr, B and Mg; M2 is one or more elements selected from Nb, Ti, Al, Mo, W, Ta, V and La; 0.6≦a1<1, 0<b1≦0.4, 0<c1≦0.4, 0≦d1≦0.1, 0≦e1≦0.1, and a1+b1+c1+d1+e1=1, The first shell portion has a composition represented by the following chemical formula 2: [Chemical formula 2] [Nia2Cob2Mnc2M1d2](OH)2 In the above Chemical Formula 2, M1 is one or more elements selected from Zr, B and Mg; 0.6≦a2<1, 0<b2≦0.4, 0<c2≦0.4, 0≦d2≦0.1, and a2+b2+c2+d2=1, The second shell portion has a composition represented by the following chemical formula 3: [Chemical formula 3] [Ni a3 Co b3 Mn c3 M1 d3 M3 f3 ] (OH) 2 In the above Chemical Formula 3, M1 is one or more elements selected from Zr, B and Mg; M3 is one or more elements selected from Nb, Ti, Al, Mo, W, Ta, V and La; A positive electrode active material precursor, wherein 0.6≦a3<1, 0<b3≦0.4, 0<c3≦0.4, 0≦d3≦0.1, 0<f3≦0.1, and a3+b3+c3+d3+f3=1.

2. The positive electrode active material precursor according to claim 1 , wherein the first shell portion has a thickness of 1 μm or more and 9 μm or less.

3. The positive electrode active material precursor according to claim 1 , wherein the second shell portion has a thickness of 0.5 μm or more and 2 μm or less.

4. A method for producing the positive electrode active material precursor according to claim 1, comprising the steps of: (A) continuously introducing a transition metal-containing solution containing nickel (Ni), cobalt (Co) and manganese (Mn) ions, an ammonium cation complex forming agent and a basic solution into a reactor to cause a coprecipitation reaction to form a first core portion; (B) continuously introducing the transition metal-containing solution, an ammonium cation complexing agent, and a basic solution into a reactor containing the first core portion to cause a coprecipitation reaction to form a first shell portion on the first core portion; (C) continuously introducing the transition metal-containing solution, the ammonium cation complex forming agent, the basic solution and a third doping solution containing M3 (one or more elements selected from Nb, Ti, Al, Mo, W, Ta, V and La) ions into a reactor containing the first shell portion formed on the first core portion, and co-precipitating the third doping solution to form a second shell portion on the first shell portion; The method for producing a positive electrode active material precursor, wherein the coprecipitation reaction in the step (B) is carried out at a lower pH than the coprecipitation reaction in the step (A).

5. 5. The method for producing a cathode active material precursor according to claim 4, wherein in step (A), a first doping solution containing M1 (one or more elements selected from Zr, B, and Mg) ions, a second doping solution containing M2 (one or more elements selected from Nb, Ti, Al, Mo, W, Ta, V, and La) ions, or a combination thereof is further added and subjected to a coprecipitation reaction to form a first core portion.

6. 5. The method for producing a cathode active material precursor according to claim 4, wherein in step (B), a first doping solution containing M1 (one or more elements selected from Zr, B, and Mg) ions is further added to cause a coprecipitation reaction to form a first shell portion on the first core portion.

7. 5. The method for producing a cathode active material precursor according to claim 4, wherein in step (C), a first doping solution containing M1 (one or more elements selected from Zr, B, and Mg) ions is further added to cause a coprecipitation reaction to form the second shell portion on the first shell portion.

8. They are spherical secondary particles formed by agglomeration of primary particles, a second core portion made of randomly oriented primary particles, a third shell portion formed on the second core portion and made of rod-shaped primary particles whose (003) planes are oriented in a direction from the center of the secondary particle toward the surface, and a fourth shell portion formed on the third shell portion and made of randomly oriented primary particles, It has a composition represented by the following chemical formula 4: [Chemical formula 4] Li x [Ni a4 Co b4 Mn c4 M1 d4 M2 e4 M3 f4 ]O 2 In the above Chemical Formula 4, M1 is one or more elements selected from Zr, B and Mg; M2 and M3 are each independently one or more elements selected from Nb, Ti, Al, Mo, W, Ta, V, and La; A positive electrode active material, wherein 0.9≦x≦1.2, 0.6≦a4<1, 0<b4≦0.4, 0<c4≦0.4, 0≦d4≦0.1, 0≦e4≦0.1, 0<f4≦0.1, and a4+b4+c4+d4+e4+f4=1.

9. The positive electrode active material according to claim 8 , wherein the primary particles forming the second core portion are spherical primary particles.

10. The positive electrode active material according to claim 8 , wherein the primary particles forming the fourth shell portion are spherical primary particles.

11. The positive electrode active material according to claim 8 , wherein the third shell portion has a thickness of 1 μm or more and 9 μm or less.

12. The positive electrode active material according to claim 8 , wherein the fourth shell portion has a thickness of 0.5 μm or more and 2 μm or less.

Citation Information

Patent Citations

  • Positive electrode active material for secondary battery, method for producing the same, and secondary battery including the same

    JP2018515884A

  • Positive electrode active material for secondary battery, method for producing the same, and secondary battery including the same

    JP2018531500A

  • Cathode active material for lithium secondary battery, method for manufacturing the same and lithium secondary battery having positive electrode including cathode active material

    JP2019200991A

  • Nickel-based active material precursor for lithium secondary battery, method for producing the same, nickel-based active material formed therefrom for lithium secondary battery, and lithium secondary battery including positive electrode including the same

    JP2020064858A

  • Positive active material for rechargeable lithium battery, method of preparing the same, and rechargeable lithium battery including the same

    JP2020087925A